The Students’ Emotional Awareness and Character Building in a Multicultural Islamic Elementary School - Kholis, Nur; Remanita, Yuan; Indriharta, Lilik; Fathoni, Irgi Aqilul (UIN Sunan Kalijaga Yogyakarta, 2026)
Emotions play a fundamental role in learning; however, character-building studies in elementary education still tend to emphasize cognitive and behavioral aspects, with limited attention to students’ lived emotional experiences, particularly in multicultural contexts. This study aims to explore how students experience emotional awareness as part of their learning processes in a multicultural Islamic elementary school. A qualitative phenomenological approach was employed at SDI Al-Azhar Tulungagung. The study involved ten informants, consisting of five students, three teachers, and two school principals, selected purposively to represent diverse perspectives. Data were collected through in-depth interviews, participatory observations, and documentation, and analyzed using phenomenological procedures, including data reduction, meaning unit development, and essential interpretation. The findings reveal that students develop emotional awareness through processes of recognising, managing, and reflecting on emotions arising in daily classroom interactions. Emotional awareness functions as a foundation for self-regulation, empathy, responsibility, and prosocial behaviour, which emerge through safe and supportive learning environments. Three essential themes were identified: (1) emotional recognition as an initial awareness of internal states triggered by classroom interactions, (2) emotional regulation as a socially mediated process shaped by teacher support and peer relationships, and (3) emotional reflection as a meaning-making process connecting experiences to moral values. These findings highlight that emotional awareness is not merely an individual competence but an intersubjective process constructed through social and cultural interactions in a multicultural learning environment. This study contributes to a deeper understanding of emotional dynamics in elementary education by emphasising the role of lived experience in character formation.